γ-Aminobutyric acid production by selected lactic acid bacteria isolate of an Indonesian indigenous fermented buffalo milk (dadih) origin - Harnentis Harnentis; Nurmiati Nurmiati; Yetti Marlida; Frederick Adzitey; Nurul Huda (Veterinary World, 2019)
Aim: This study aimed at optimizing γ-aminobutyric acid (GABA) production using lactic acid bacteria (LAB) of an Indonesian indigenous fermented buffalo milk (dadih) origin. This study utilized LAB previously cultured from dadih that has the ability to produce GABA.